Fraud Detecting Using Beneish M-Score and F-Score: Which is More Effective? - Husnurrosyidah, Husnurrosyidah; Fatihah, Inayatul (EQUILIBRIUM, 2022)
Beneish M-Score and F-Score are methods of identifying fraud in financial statements. The difference in research results between the two methods requires an in-depth study of the effectiveness of the Beneish M-Score and F-Score methods for detecting fraud. The type of research is descriptive and quantitative. The population in this study were companies registered in JII from 2017-2021. Through purposive sampling, ten sample companies were obtained. The results revealed that the Beneish M-Score method is more effective in detecting fraud in JII-registered companies in 2017-2021 than the F-Score. Evidenced by a higher level of accuracy and lower error type than the F-score method. However, the F-Score method has weaknesses in the level of accuracy and type error. Therefore, the Beneish M-Score helps regulators and auditors detect fraud in financial statements, so it is very important for potential investors to be able to make the right investing decisions.